Analisis Literasi Teknologi Guru Bimbingan Dan Konseling Se-DKI Jakarta Menghadapi Era Industri 4.0 - Hermawan, Dede; Aisyah, Syifa; Khoirunnissa, Khoirunnissa (STKIP Andi Matappa, 2019)
Technology literacy is the capacity to operate, manage, assess and realize the technology is. This study aims to determine an empirical description of the level of technological literacy owned by counselor/counseling teacher in Jakarta. This research uses a quantitative approach with descriptive research methods.The data collection was worked out using by technology literacy instruments by taking a sample from 157 junior high school with counseling teachers around DKI Jakarta. The results of the research related to the level of technological literacy showed that 61.14% of counseling teachers were in the top categories, which iz 35.03% in the sufficient category and 3.82% in the low and very low categories.